Assessment of the C1 Lateral Mass Screw Trajectory and Position Using Plain Radiographs: A Comparison With Computed Tomography. Issue 3 (April 2016) - Lee, Sang-Hun; Park, Dae-Hyun; Kim, Man-Ho; Huh, Dae-Seok; Kang, Kyung Chung; Lee, Jung-Hee; Suk, Kyung-Soo; Kim, Ki-Tack
Abstract : Study Design: A prospective study. Objective: The aim of this study was to provide methods for predicting ideal trajectory and position of C1 lateral mass screw (C1LMS) from plain radiographs. Summary of Background Data: There has been no study on prediction of C1LMS position using plain radiographs. Methods: A total of 40 consecutive subjects (with 79 screws) who had undergone C1LMS placement were enrolled. To evaluate the C1LMS position, the positions of screw head and tips on anteroposterior radiographs, screw length, and height on lateral radiograph were graded as 0, I, and II, respectively. On the postoperative computed tomography images, we analyzed lateral mass (LM) perforation, screw-thread engagement percent (%), bicortical fixation, extruded screw length, and violation of adjacent joints. Results: Screws with tip located medial to LM (tip 0) showed LM perforation in all cases. Polyaxial head located within the LM (head 0) or crossing the lateral margin of the LM (head I) showed no LM perforation. Screw-thread engagement percent was the highest with head I-tip I (medial half of LM) position (97.6%), followed by head 0-tip I (90.5%) and head I-tip II (lateral half of LM) (86.4%). Screws longer than the posterior half of C1 anterior arch (AA) showed bicortical fixation in all cases with mean extruded screw length of 1.9 mm. Adjacent joint was not violated in 98%, with the screw height below half of C1AA. Conclusions: On an anteroposterior radiograph, a C1LMS with the screw head located on the lateral margin of the LM and with the screw tip in the medial half of the LM resulted in the safest and longest trajectory. On lateral radiograph, a screw tip that is placed within the anterior-inferior quadrant of the C1AA results in safe bicortical fixation without injury to the adjacent structures. These plain radiographic findings may be helpful both postoperatively and intraoperatively for assessing the trajectory and length of the screw.